Trace Element Uptake Dynamics for Maize (Zea Mays L.) Grown Under Field Conditions - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N (2013)
Background and aims: The trace element uptake process of plants is a key factor in assessing the risks of trace element build-up in agricultural soils. Scarce information exists on the trace element dynamic uptake of plants grown in the field, especially on those potentially hazardous. In this study, the uptake process of As, Cd, Cu, and Zn in maize plants was quantified and characterized throughout the entire season. Methods: Along two seasons, the uptake dynamics of field-grown maize plants in absorbing the soil borne trace elements was examined. Biomass production and the concentration of the elements in plant and soil solution samples were determined. A kinetic model was employed to characterize the uptake by plants. Results: The kinetic parameters of the uptake process, maximum cumulative uptake rate, U max, time to reach 50 % of U max, t U50, and reciprocal of the uptake rate, b U when followed throughout the season in terms of the plant s growing degree days remained constant between seasons and were element specific. In spite of the large amount biomass produced, maize plants extracted minute quantities of Cd and As. Increasing cumulative uptake rates of As, Cd, Cu, and Zn from the soil took place primarily in the early half of the growing season when the biomass accumulation was still less than 50 % of the maximum harvested biomass. The element-specific plant uptake factor (PUF), which denote the partition of trace elements between the soil solution and plant phases, decreased following a first-order kinetics along the growing period, did not show any significant difference between seasons, and, at maturity stage, followed the sequence Cd?Zn>Cu?As. Conclusions: The uptake process of the elements was adequately described by the kinetic model, showing similar patterns but different magnitude and distribution in the plant. The extraction of Cd and As by plants is low in comparison to common inputs through fertilizer applications into maize production systems, indicating potential risk of trace element accumulation in soils. The PUF may be estimated according to the kinetics parameters of the uptake process. On a per-unit-soil solution element basis, Cd and Zn would be more susceptible to the soil-to-plant transfer than As and Cu. © 2013 Springer Science+Business Media Dordrecht.